2019
DOI: 10.1002/jls.21655
|View full text |Cite
|
Sign up to set email alerts
|

Advancing the Transformational–Transactional Model of Effective Leadership: Integrating two Classic Leadership Models with a Video‐Based Method

Abstract: The presented empirical study demonstrates that the predictive validity of Bass' “transformational‐transactional” model of leadership can be enhanced by incorporating certain aspects of the older Ohio State “initiating structure‐consideration” model of leadership. A precise, fine‐grained video‐based method shows that “initiating structure” behaviors (e.g., directing, informing, structuring) explained the variance in leader and team effectiveness better than “transactional behavior.” Thus, a refined version of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 112 publications
(171 reference statements)
0
12
0
3
Order By: Relevance
“…Third, the mediating effect of individual innovation readiness between TFL and IWB corroborates prior research by Eisenbeiß and Boerner (2010), who showed that transformational leaders stimulate IWB by increasing employees' confidence in their own innovative behaviours. Thus, future research could delve even deeper into the innovation effects of certain observable micro‐behaviours of both transformational leaders (Hoogeboom & Wilderom, 2019; Van Dun et al, 2017; Yukl, 2012) and followers (Qu et al, 2015; Van Dun & Wilderom, 2021) on employee IWB, including the perception that there are sufficient resources for innovation and employee readiness to innovate. Even more of such refined behavioural insights could eventually propel more workers towards IWB.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the mediating effect of individual innovation readiness between TFL and IWB corroborates prior research by Eisenbeiß and Boerner (2010), who showed that transformational leaders stimulate IWB by increasing employees' confidence in their own innovative behaviours. Thus, future research could delve even deeper into the innovation effects of certain observable micro‐behaviours of both transformational leaders (Hoogeboom & Wilderom, 2019; Van Dun et al, 2017; Yukl, 2012) and followers (Qu et al, 2015; Van Dun & Wilderom, 2021) on employee IWB, including the perception that there are sufficient resources for innovation and employee readiness to innovate. Even more of such refined behavioural insights could eventually propel more workers towards IWB.…”
Section: Discussionmentioning
confidence: 99%
“…The current three-factor structure is distinct from previously proposed three-factor models (Den Hartog et al, 1997 ; Avolio et al, 1999 ; Heinitz et al, 2005 ; Kanste et al, 2007 ; Edwards et al, 2012 ) in terms of factor content, explained variance, and interpretability. In previous studies, the first factor was most often represented by transformational and CR subscales (e.g., Den Hartog et al, 1997 ) due to their high intercorrelation (Hoogeboom and Wilderom, 2019 ). The second factor usually included either MBEA or MBEP items, or the mixture of both (e.g., Kanste et al, 2007 ; Edwards et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Akin to the leadership field in general—and as seen particularly in the network leadership field—little is known about the specific behaviors that fit the leadership roles: The actual behavioral repertoires associated with effective network leadership should be considered as a novel line of research. The video‐observation method, preferably including video‐shadowing in other (less formal) work settings (Czarniawska, 2007; Vie, 2010), would be particularly useful for studying network leaders (Hoogeboom & Wilderom, 2019).…”
Section: Theoretical Implications and Suggestions For Future Researchmentioning
confidence: 99%